BIBLIOGRAPHY OF QUATERNARY AFRICAN PALAEONTOLOGY - Welbourne, Robert G. (BERNARD PRICE INSTITUTE FOR PALAEONTOLOGICAL RESEARCH, 1969)
The bibliography of Hopwood and Hollyfield 1954 listed the fruits of African palaeontological research over the 200 years up to the end of 1950. This work is very full and is the basic work in its field. Since it came out, however, only one partial revision has appeared: that of Savage 1956, which merely lists species without giving any references. The work of Hopwood and Hollyfield is now nearly 20 years old and badly needs a supplement. My aim in compiling this bibliography was to meet this need.